KINERJA PEMERINTAH KELURAHAN DALAM MENINGKATKAN PELAYANAN PUBLIK (Suatu Studi di Kelurahan Tingkulu Kota Manado) - SUMARSONO, KOSARINA D. (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: the role of the Government is indeed changing in accordance with the demands of agrowing community and dynamics. Although the role of the Governmentis experiencing many changes in the Government's task is to give shortmaids the best to thecommunity. The purpose of this study is: to know how the performance of the Government inimproving public services in kelurahan Tingkulu Sub Wanea ManadoThe type of research used in this research is qualitative research. qualitative research is the kindof research that producesinventions that cannot be reached (obtained) byusing statistical procedures or other ways of quantifying (the measurement). Sampling in thisresearch that became an informant and is determined based on Purposive Samplingtechnique,namely the determination of the sample by consideration or particular criteria, so the numberof informants thatthere are as many as 10 people.The results showed Tingkulu village government performance in improving public services is still lesswell seen from theperformance indicators used are: (1) productivity, Accountability (2), (3) the qualityof service, Responsiveness (4), (5)corporate responsibility.Keywords: performance, public services